Chapter Occupational Exposure to Magnetic Field inTranscranial Magnetic Stimulation Treatment - Jacob Møllerløkken, Ole (InTechOpen, 2018)
Transcranial magnetic stimulation (TMS) is used both as a diagnostic instrument and for therapy, available only at some psychiatric clinics for treatment of depression and at clinical neurophysiology where TMS is used for diagnosis of nerve damage. The Swedish National Board of Health and Welfare issued a referral edition about the use of repetitive TMS as an alternative treatment for depression. This may lead to a major increase in the application of TMS to treat depression. TMS is based on induction of an electric (E) field inside the brain by application of an external magnetic field with rapid rise and fall time. The E field in the brain has been calculated when different coils were used for the treatment. The reported E fields are of the order of tens to hundreds of volts per meter and the induced current density is estimated at tens of A/m2. This field can depolarize neurons or modulate cortical excitability by selecting the appropriate parameters for stimulation and the duration of the treatment session. The mechanisms of action of neurostimulation still remain incompletely understood.